Valuing ecosystem services : methodological issues and case studies - Ninan, K. N.; Costanza, Robert
"Conserving biodiversity and ecosystem services is critical to promoting human welfare and sustainable development. Valuing Ecosystem Services: Methodological Issues And Case Studies presents the latest research on valuing ecosystem services and case studies by leading experts from around the world. This thought provoking book draws together prominent international authorities to discuss the key methodological issues and challenges in valuing ecosystem services. Covering a cross-section of ecosystems and services in different sites, countries and regions, and presenting state of the art surveys of studies on valuation of forest and coastal ecosystems and pollination services, the collection presents essential case studies that value ecosystem services and experiences with operationalising valuation into policy. Providing a unique blueprint for moving the science and practice of ecosystem services valuation forward, this timely book will be of special interest to academics, policy makers and professionals working in ecological economics, natural resources, forestry and conservation."--Page 4 of cover.